PELAKSANAAN DAN PENGAWASAN PROGRAM (BOSDA) DI SEKOLAH DASAR NEGERI 06 KUBU RAYA - Andika Okta Wijaya E.01106067 (FISIP Universitas Tanjungpura, 2013)
The purpose of this study was to determine on evaluation of the implementation proces of BOSDA in SDN 06 Kecamatan Sungai Raya Kabupaten Kubu Raya. Using qualitative methods and wih a descriptive approach. In the implementation of these activites, there are still many ostacles, ither because the manufacture and the pletion of this accouantability report is not accordance as expected and lack of sepervision from the BOSDA team. So that resulting in delaying submission of accouantability reports. Based on this reseacrh, the way this to fix this policy is supporting each other the implemitation of policies implemented in school. Monitoring should be done regularly. Principles must be able to arrange financing patterns and utilizatoin of funds BOSDA operating in efficienly, so that the implemenation of this policy can be felt by society. Key Word : Implemenation BOSDA, Evaluation BOSDA